The Dopamine D1 Receptor Attenuates Titanium Particle-Induced Inhibition of Osteogenesis by Activating the Wnt Signaling Pathway - Chengcheng Feng; Yajun Li; Minhui Gu; Wenming Li; Yunshang Yang; Shuangshuang Chen; Yong Ma; Dechun Geng; Long Xiao; Zhirong Wang (Hindawi Limited, 2023)
Periprosthetic osteolysis (PPO), caused by wear particles, has become a major cause of joint replacement failure. Secondary surgery after joint replacement poses a serious threat to public health worldwide. Therefore, determining how to effectively inhibit wear particle-induced PPO has become an urgent issue. Recently, the interaction between osteogenic inhibition and wear particles at the biological interface of the implant has been found to be an important factor in the pathological process. Previous studies have found that the central nervous system plays an important role in the regulation of bone formation and bone remodeling. Dopamine (DA), an important catecholamine neurotransmitter, plays an integral role in the physiological and pathological processes of various tissues through its corresponding receptors. Our current study found that upregulation of dopamine first receptors could be achieved by activating the Wnt/β-catenin pathway, improving osteogenesis in vivo and in vitro, and significantly reducing the inhibition of titanium particle-induced osteogenesis. Overall, these findings suggest that dopamine first receptor (D1R) may be a plausible target to promote osteoblast function and resist wear particle-induced PPO.